2018
DOI: 10.1053/j.gastro.2018.08.022
|View full text |Cite
|
Sign up to set email alerts
|

FXR-Dependent Modulation of the Human Small Intestinal Microbiome by the Bile Acid Derivative Obeticholic Acid

Abstract: In studying the effects of OCA in humans and mice, we found evidence for interactions between bile acids and features of the small intestinal microbiome. These findings indicate that farnesoid X receptor activation alters the intestinal microbiota and could provide opportunities for microbiome biomarker discovery or new approaches to engineering the human microbiome. ClinicalTrials.gov, NCT01933503.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 41 publications
6
78
0
Order By: Relevance
“…HFD was shown to induce increased phylum Firmicutes or the Firmicutes/Bacteroidetes ratio, whereas BD surgery enhanced Bacteroidetes in WT mice (4). Recent findings showed that FXR activation altered gut microbiota composition in humans (37). The current data show a distinct distribution of cecal microbiota in LFD-and HFD-fed FXRko mice with a decrease of phylum Bacteroidetes.…”
Section: Discussionsupporting
confidence: 46%
“…HFD was shown to induce increased phylum Firmicutes or the Firmicutes/Bacteroidetes ratio, whereas BD surgery enhanced Bacteroidetes in WT mice (4). Recent findings showed that FXR activation altered gut microbiota composition in humans (37). The current data show a distinct distribution of cecal microbiota in LFD-and HFD-fed FXRko mice with a decrease of phylum Bacteroidetes.…”
Section: Discussionsupporting
confidence: 46%
“…In a phase 1 RCT in man, treatment with obeticholic acid for 17 days, that suppressed bile acid synthesis, produced a reversible induction of Gram-positive bacteria that are found in the small intestine. There was also an increase in the representation of microbial genomic pathways involved in DNA synthesis and amino acid metabolism with obeticholic acid treatment [158].…”
Section: Obeticholic Acid and Other Drugsmentioning
confidence: 98%
“…The use of BA receptor agonists and antagonists and their indirect effects (BA pool, synthesis, circulation, and the gut microbiome composition) is summarized in Figure 2. The human and mouse gut microbiome fluctuates with the increase or decrease of BAs, which can lead to increased inflammation and intestinal malabsorption (19,37,80,(84)(85)(86). In depth exploration of BA signaling and circulation during chronic liver diseases may provide insight to disease amelioration or treatment strategies.…”
Section: Resultsmentioning
confidence: 99%